An impulsive noise analyser using amplitude probability distribution (APD) for broadband-wired communication - Zainal Abidin, Ahmadun Nijar (2011)
Electromagnetic interference or noise which is of impulsive nature is known to affect data communication performance. It is useful to correlate the characteristics of the noise with the bit error probability (BEP). The amplitude probability distribution (APD) has been proposed within CISPR for characterisation of the impulsive noise. However, there is no analyser available to perform direct measurement of the noise within the bandwidth of asymmetric digital subscriber line (ADSL2+) communication. This research presents a novel development of APD analyser for measurements of impulsive noise emission and its impact on ADSL2+ communication. A unique noise APD pattern is obtained from each measurement of noise emission from different electrical and electronic appliances. It is vital to have correct measurement set-up, signal power level, sampling rate, sample points and filter characterisation in order to acquire accurate data representation of the noise patterns. The APD graph is generated by the analyser using the APD algorithm method which employs the envelope sampling technique from actual probability. The noises are characterised using α-stable distribution which exhibits its own distinct APD parameters. The APD curve can be related with the single modulation scheme communication channel performance for estimation of bit error probability. The analyser has been developed successfully with dynamic range of 70 dB higher than the 60 dB CISPR 16 requirement, 0.02 dB amplitude resolution compared to 0.25 dB CISPR 16 requirement and 0.59 dB amplitude accuracy compared with the CISPR 16 standard of +/- 2.7 dB. In addition, the limits for noise in copper cable have been proposed for estimating the severity of the interference towards digital communication performance in ADSL2+ system. An advantage of the analyser is its ability to not only record the noise but the ability to regenerate back the noise which can be used for further analysis. In conclusion, the analyser can provide a comprehensive platform for impulsive noise interference verification towards ADSL2+ communication performance.